Atlas web mapping of hazardous hydrometeorological events in the Ural Prikamye region - Shikhov, A.N.; Abdullin, R.K. (Perm Federal Research Centre Journal, 2019)
The paper presents the designing and development of the Atlas Information System (AIS) of hazardous hydrometeorological events (HHME) in the Ural Prikamye region. AIS integrates classic mapping approaches and modern web mapping service technologies. AIS information basis includes several data sources, both ground-based and satellite observations. The basic techniques and algorithms for mapping of HHME spatiotemporal distribution and the main AIS content are briefly described. Examples are provided of periodicity and intensity mapping of various HHME types, as well as zoning results of the study area in terms of prevailing types of hazardous weather events. The AIS content functionality is considered, including various techniques of data visualization, connection to external databases, search and query generation, building of cartograms and structural diagrams. AIS is published in open access as cartographic web map service (http://ais.maps.psu.ru). The main result of the project for the Perm region is the development of the unique reference and information cartographic resource on the current climatic conditions of the region, its typical HHME, their spatiotemporal distribution, as well as HHME-related damage.